2018
DOI: 10.1111/exd.13791
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome of the “sterile” pustules in palmoplantar pustulosis

Abstract: The skin microbiome influences skin pathophysiology. Palmoplantar pustulosis (PPP) is a chronic skin disease characterized by infectious‐like pustules on the palms and soles. These pustules are thought to be sterile because bacterial cultures obtained from the pustules are negative. However, culture methods are limited in their ability to identify all bacteria on the skin. We hypothesized that the “sterile” pustules of PPP do not lack bacteria, but rather contain a microbiome. To test this hypothesis, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…To determine if bacteria were present in the PPP pustules, we used the 16S small subunit ribosomal gene . We found no bacterial DNA in the pustules, contrary to the report of Masuda‐Kuroki et al . We used the primer set for a full‐length sequence of the nine specific regions (V1–V9) due to the accurate taxonomic classification, whereas Masuda‐Kuroki et al .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To determine if bacteria were present in the PPP pustules, we used the 16S small subunit ribosomal gene . We found no bacterial DNA in the pustules, contrary to the report of Masuda‐Kuroki et al . We used the primer set for a full‐length sequence of the nine specific regions (V1–V9) due to the accurate taxonomic classification, whereas Masuda‐Kuroki et al .…”
Section: Discussionmentioning
confidence: 79%
“…used primers specific to the V1–V2 region, which can yield a positive result. In addition, Masuda‐Kuroki et al . reported that bacterial DNA fragments were detected in the vesicular fluid but not in the pustular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, only six children with TMEP have been reported. 1 We herein report a child with TMEP with characteristic linear distribution following Blaschko lines.…”
Section: Child Case Of Linear Variant Of Telangiectasia Macularis Erumentioning
confidence: 89%
“…2 Levels of both IL-23 and Th17-derived cytokines, such as IL-17 and IL-22, are upregulated in PPP lesions, suggesting a similar Th17-mediated cytokine circumstance to psoriasis. 1 However, secukinumab, an IL-17A inhibitor, did not show the effectiveness against PPP, in contrast to the excellent effect on psoriasis. 3 In the present case, the GPP lesions had completely been remitted by secukinumab therapy, but not PPP lesions.…”
mentioning
confidence: 98%
See 1 more Smart Citation